Oxidative Stress, Inflammation, and Mitochondrial Dysfunction: A Link between Obesity and Atrial Fibrillation - Alkora Ioana Balan; Vasile Bogdan Halațiu; Alina Scridon (Antioxidants, 2024)
The adipose tissue has long been thought to represent a passive source of triglycerides and fatty acids. However, extensive data have demonstrated that the adipose tissue is also a major endocrine organ that directly or indirectly affects the physiological functions of almost all cell types. Obesity is recognized as a risk factor for multiple systemic conditions, including metabolic syndrome, type 2 diabetes mellitus, sleep apnea, cardiovascular disorders, and many others. Obesity-related changes in the adipose tissue induce functional and structural changes in cardiac myocytes, promoting a wide range of cardiovascular disorders, including atrial fibrillation (AF). Due to the wealth of epidemiologic data linking AF to obesity, the mechanisms underlying AF occurrence in obese patients are an area of rich ongoing investigation. However, progress has been somewhat slowed by the complex phenotypes of both obesity and AF. The triad inflammation, oxidative stress, and mitochondrial dysfunction are critical for AF pathogenesis in the setting of obesity via multiple structural and functional proarrhythmic changes at the level of the atria. The aim of this paper is to provide a comprehensive view of the close relationship between obesity-induced oxidative stress, inflammation, and mitochondrial dysfunction and the pathogenesis of AF. The clinical implications of these mechanistic insights are also discussed.